A case study on the behavior of the visually imparied with color and lighting as aids in successful wayfinding and navigation in shopping malls - Ong, Jhoanna Loreine B. author
This study mainly focused on how the visually impaired behave with interior elements, particularly color and lighting in their wayfinding and navigation in shopping malls. Ten 10 visually impaired respondents with different low vision conditions, excluding the bilaterally blind and those subjected to total loss of vision, were observed and interviewed in two selected shopping malls-UP Town Center and Robinsons Galleria. The principles of Universal Design and Theory of Accessibility were used as framework and basis for the analysis. Through field research and indepth interview, the study was able to gather qualitative data. Verbal Protocol Analysis VPA was utilized for the field research. The study resulted to a variety of themes but in summary, the visually impaired relied heavily on color contrast applied in store graphic signage in their wayfinding and navigation. Lighting has a considerable effect in making the space brighter and more vivid affecting the clarity of space perception. Universal Design affirmed that the interior design of the shopping malls complied with its principles. The spatial layout of the interior mall space conformed to the principles of the theory of accessibility but the perception of the respondents stated otherwise. Other wayfinding and navigation factors graphic signage, spatial layout, merchandise and branding, and materialeither helped or hindered the visually impaired relating to color and lighting. In conclusion, the visually impaired encountered wayfinding and navigation decision situations as they identify and choose wayfinding and navigation systems, cues or aids to rely on. They heavily relied on color and lighting specifically through color contrast and clarity perception. Their level of awareness towards color and lighting is believed to be average to above average.